PENGARUH INTENSITAS KOMUNIKASI DAN POLA KOMUNIKASI KELUARGA KONSENSUAL TERHADAP KELEKATAN ORANG TUA-ANAK PADA KELUARGA LONG DISTANCE MARRIAGE - Zulfa Priastuti, Nadia; Luqman, Yanuar; Noor Rakhmad, Wiwid (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Effective communication is crucial for maintaining harmonious relationships, especially in long-distance marriages. With the rise of migrant workers, many families face long-distance relationships that can impact parent-child bonds. This study examines how family communication intensity and patterns affect parent-child attachment in such families, using attachment theory and family communication patterns theory. Through a survey of 96 respondents and simple linear regression analysis, the results of hypothesis testing show that communication intensity can explain 33.4% with an effect size of 0.839 and consensual family communication patterns can explain 21.5% with an effect size of 0.546 on parent and child attachment. It can be concluded that higher communication intensity and consensual communication patterns significantly enhance parent-child attachment. The results suggest that frequent and open communication, as well as consensual communication patterns, can help strengthen parent-child relationships despite physical separation.